Influence of transoesophageal echocardiography on therapy and prognosis in young patients with TIA or ischaemic stroke - Rettig, T.C.D. (Bohn Stafleu van Loghum, 2009)
Objective. To determine the influence of transoesophageal echocardiography (TEE) on therapy and prognosis in patients with cryptogenic transient ischaemic attack (TIA) or ischaemic stroke under the age of 50 years. Methods and results. We evaluated all patients aged 50 and under who were referred to our university hospital for cryptogenic TIA or ischaemic stroke during the period 1 January 1996 to 31 December 2004. All patients underwent both transthoracic echocardiography (TTE) and TEE. Patients with known pre-existent heart disease, such as atrial fibrillation, were excluded. Eighty-three patients with TIA (22) and ischaemic stroke (61) were enrolled. Mean age was 39±8 years (range 18 to 50). In 30% of the patients TEE detected one or more potential cardioembolic source, compared with 10% for TTE (p=0.003). Standard treatment (aspirin 38 mg daily) was changed in 7% of the patients due to the TEE findings. Complete followup was obtained in 93% with an average of 5±3 years. Twelve recurrences occurred; two out of six patients (33%) with therapy change and ten out of 71 (14%) of the patients without therapy change had a recurrent TIA or ischaemic Stroke. Conclusion. In patients with cryptogenic TIA or ischaemic stroke, TEE is superior to TTE in the detection of a potential cardiac source of embolism. However, findings obtained by TEE only influence the already initiated treatment in a small percentage of patients. The recurrence rate both in the group with and without therapy change is high. (Neth Heart J 2009;17:373-7.19949646)